150 years in the making: first comprehensive list of the ants (Hymenoptera: Formicidae) of Virginia, USA - Ivanov, Kaloyan; Hightower, Liberty; Dash, Shawn T.; Keiper, Joe B. (Zootaxa, 2019)
Due to Virginia’s geographic location, topographic variability, and diversity of physiographic provinces, the state ranks as one of the most biodiverse areas in the US. Virginia’s myrmecofauna, however, has been insufficiently studied and is not well known. Here we present the first comprehensive list of the ants of Virginia and provide county-level distributions for all taxa. With taxonomic updates taken into account, review of published records revealed that 130 species have been reported from the state. We add another 34 species based on newly collected materials, review of museum and personal collections, and online databases. At present, 164 species and morphospecies, including 15 ant exotics, are known to occur in the state. Another 12 species are provisionally excluded from the list as they represent distribution anomalies, or are based on erroneous records. The work presented here is an initial step towards a more complete treatment of the identification, taxonomy, and natural history of the ant fauna of Virginia.